2009
DOI: 10.1111/j.1365-294x.2009.04394.x
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex variation at class II DQA locus in the brown hare (Lepus europaeus)

Abstract: The major histocompatability complex (MHC) is a multigene family of receptors that bind and present antigenic peptides to T-cells. Genes of the MHC are characterized by an outstanding genetic polymorphism, which is considered to be maintained by positive selection. Sites involved in peptide binding form binding pockets (P) that are collectively termed the peptide-binding region (PBR). In this study, we examined the level of MHC genetic diversity within and among natural populations of brown hare (Lepus europae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 69 publications
1
42
5
Order By: Relevance
“…Our results contrast with others where support for NFDS and FSP have been reported (Westerdahl et al, 2004;Dionne et al, 2009). However, there is evidence for diversifying selection in space in Brown hare Koutsogiannouli et al, 2009). Indeed, differences in climate and parasite composition between the regions seem to have created contrasting selection regimes at class II MHC loci (Smith et al, 2009).…”
Section: Tablecontrasting
confidence: 99%
“…Our results contrast with others where support for NFDS and FSP have been reported (Westerdahl et al, 2004;Dionne et al, 2009). However, there is evidence for diversifying selection in space in Brown hare Koutsogiannouli et al, 2009). Indeed, differences in climate and parasite composition between the regions seem to have created contrasting selection regimes at class II MHC loci (Smith et al, 2009).…”
Section: Tablecontrasting
confidence: 99%
“…Due to the underrepresentation of Greek populations in MHC class II studies and in the IMGT/HLA Database [24] as well as the low sample size of the existing studies, ethnic-specific rare alleles could have been “missed out”. On the other hand, the existence of population-specific alleles suggests that differential selective pressures maintained these MHC allelic differences [28]. It has been shown that population-specific variation at the HLA class I loci is positively correlated with local pathogen richness [29].…”
Section: Discussionmentioning
confidence: 99%
“…No relationship was found between breeds feature and MHC class Iα gene in phylogenetic trees. Similarly, Koutsogiannouli et al (2009) surveyed the level of MHC genetic diversity of European and Asia brown hares (Lepus europaeus) in natural populations, and did not find a strong phylogeographic signal in the full-length exon 2eeu-DQA alleles' phylogeny. Xu et al (2009) found that three MHC alleles (DQB, DRA and MHC-I) of cetaceans showed similarity and identity when compared with the phylogenetic trees.…”
Section: Discussionmentioning
confidence: 99%
“…Fax: 0086-551-5786013. and Yang, 2008;O'Leary et al, 2009), whales (Xu et al, 2009) wild animals (Koutsogiannouli et al, 2009;Becker et al, 2009) and avian (Ewald and Livant, 2004;Westerdahl et al, 2000).…”
Section: Introductionmentioning
confidence: 99%